2022
DOI: 10.1021/acsnano.2c04840
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based SARS-CoV-2 and Variants Detection System using Colorimetric DNAzyme Reaction Triggered by Loop-Mediated Isothermal Amplification (LAMP) with Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)

Abstract: Coronavirus disease (COVID-19) has affected people for over two years. Moreover, the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants has raised concerns regarding its accurate diagnosis. Here, we report a colorimetric DNAzyme reaction triggered by loop-mediated isothermal amplification (LAMP) with clustered regularly interspaced short palindromic repeats (CRISPR), referred to as DAMPR assay for detecting SARS-CoV-2 and variants genes with attomolar sensitivity within an hour.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…For example, upon binding to ssDNA or ssRNA, the trans -cleavage mechanism can release a fluorescence reporter from the quenched fluorescence probe [ 9 , 12 , 20 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Different CRISPR-Cas systems have been utilized for multiplex SARS-CoV-2 detection, including the Cas9 system (recognizes dsDNA) [ 77 , 78 ], Cas12 (recognizes both ssDNA and dsDNA) [ 9 , 71 , 72 , 75 , 76 , 79 ], and Cas13 (recognizes ssRNA) [ 12 , 20 , 71 , 74 , 80 , 81 ]. Additionally, amplification techniques, such as RT-PCR [ 9 , 71 , 72 , 76 ], RT-LAMP [ 73 , 77 , 79 ], and RT-RPA [ 9 , 20 , 75 , 78 ], are often combined with CRISPR-based detection to enhance the limit of detection (LOD) in viral detection assays.…”
Section: Multiplex Viral Rna Detection and Amplification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, upon binding to ssDNA or ssRNA, the trans -cleavage mechanism can release a fluorescence reporter from the quenched fluorescence probe [ 9 , 12 , 20 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Different CRISPR-Cas systems have been utilized for multiplex SARS-CoV-2 detection, including the Cas9 system (recognizes dsDNA) [ 77 , 78 ], Cas12 (recognizes both ssDNA and dsDNA) [ 9 , 71 , 72 , 75 , 76 , 79 ], and Cas13 (recognizes ssRNA) [ 12 , 20 , 71 , 74 , 80 , 81 ]. Additionally, amplification techniques, such as RT-PCR [ 9 , 71 , 72 , 76 ], RT-LAMP [ 73 , 77 , 79 ], and RT-RPA [ 9 , 20 , 75 , 78 ], are often combined with CRISPR-based detection to enhance the limit of detection (LOD) in viral detection assays.…”
Section: Multiplex Viral Rna Detection and Amplification Methodsmentioning
confidence: 99%
“…To double check specific mutation genes, CRISPR/Cas9 with crRNA specifically designed to recognize the target genes (WT or MT) will cleave the G-quadruplex DNAzyme, which turns off the colorimetric signal. For multiplexing, the on/off colorimetric signals of multiple genes tested in parallel were derived to determine the VOCs [ 77 ].…”
Section: Multiplex Viral Rna Detection and Amplification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As smartphones are emerging as the most promising monitoring devices, providing portability, affordability, and rapidity, they can be used as readout [ 107 , 108 , 109 , 110 ], image-processing [ 111 , 112 ], or operating tools [ 55 , 113 ] on diagnostic platforms. Furthermore, LAMP has been applied in diagnostic systems using smartphones owing to its various monitoring mechanisms, including color change, fluorescence, and turbidity, which can be implemented on smartphones.…”
Section: Devices To Monitor Lampmentioning
confidence: 99%
“…Recently, Song et al reported a smartphone application based on machine learning for checking diagnostic results [ 111 ]. The diagnosis of SARS-CoV-2 and its variants consists of a colorimetric DNAzyme reaction triggered by a LAMP amplicon with clustered regularly interspaced short palindromic repeats (CRISPR).…”
Section: Devices To Monitor Lampmentioning
confidence: 99%